Effect of Modified Soy Protein on Quality Attributes of Extended Chicken Nuggets - Muthukumar, M.; Naveena, B. M.; Kommi, Kanchana; Kulkarni , V.V. (Journal of Meat Science, 2017)
A study was conducted to assess the effect of incorporation of modified soy protein (MSP) on the functional and quality attributes of extended chicken nuggets. Negative control group nuggets were prepared by utilizing 67% meat, 10% ice flakes and other non-meat ingredients (binders, spice, condiments, etc.), whereas the positive control and MSP nuggets were prepared with 62% meat, 15% ice flakes and other non-meat ingredients. In case of MSP nuggets, 0.5% of binder was replaced with modified soy protein. No significant (p>0.05) difference in pH, emulsion stability, cooking yield, expressible water and proximate composition was observed among the negative control, positive control and modified soy protein incorporated chicken nuggets. The negative control group exhibited significantly higher (p<0.01) redness value (a*), cohesiveness, hardness, and fracturability score and lower lightness (L*) value than the positive control and MSP groups. The negative control group also showed significantly (p<0.01) higher texture and overall acceptability scores. However, the incorporation of MSP and additional water did not make any significant (p>0.05) change in the storage stability of nuggets in terms of oxidative rancidity and microbial counts compared with negative control group. The results revealed that incorporation of modified soy protein enable to reduce the proportion of meat in the chicken nuggets without adversely affecting the quality and sensory attributes.